Pengembangan Keterampilan Berbicara dengan Metode Role Playing pada Mata Pelajaran Bahasa Arab - Nurul Hidayah (Jurnal Kependidikan, 2017)
There are some problems in the learning process, for example: Students look less interested and motivated to follow the lesson, the teacher gets difficulties in arising student interest, and most students have difficulty and fear to express opinions and perform in front of the class. This condition causes students’ achievement to decrease. Such condition happen in the Arabic learning process in Madrasah Aliyah and to handle it, there should be an appropriate learning method to build effective and efficient learning. A method of learning that can be developed is role playing. Role playing is a method directed at solving problems related to human relationships, especially those involving student life in schools. Role playing can also train good and correct language mastery and strengthening competence in creative and innovative language and make students more mature in learning Arabic and behaving in their environment.